2021
DOI: 10.3390/su13179766
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Digital Strategic Orientation on Organizational Performance through Digital Competence

Abstract: In the era of the digital economy, enterprises need a comprehensive digital transformation of strategy, business, organization, competence, and operation. However, being limited themselves to the development of digital technology, previous studies mainly focused on the development and application of digital technology, single case studies, and multi-case studies of digital transformation. Few researchers systematically studied the digital transformation mechanism at the organizational level. Therefore, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 40 publications
4
24
0
2
Order By: Relevance
“…Second, digital transformation managers need to focus on building their own digital transformation capability to create new value to attain sustainable competitiveness. The better the enterprise's digital transformation, the higher the operational performance [6,8,13]. Li and Liu [40] also found that a dynamic capability positively affects competitive advantage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, digital transformation managers need to focus on building their own digital transformation capability to create new value to attain sustainable competitiveness. The better the enterprise's digital transformation, the higher the operational performance [6,8,13]. Li and Liu [40] also found that a dynamic capability positively affects competitive advantage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in many research situations, such as digitization and innovation [17,24,29,30]. According to Yu and Moon [8], digital strategic orientation refers to the overall strategic direction of an enterprise in the context of digital transformation, including the strategic measures to achieve it. This study is aimed at the current digital environment, based on digital strategic orientation studies, explaining the relationship between strategic orientation (customer orientation and technology orientation) and the digital transformation capability.…”
Section: Research Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Peningkatan kinerja karyawan juga pada akhirnya berekses pada kenaikan gaji atau kompensasi sebagai konseksuensi logisnya (Reza Putra & Gupron, 2020). Lebih lanjut, (Almusaddar et al, 2018;Yu & Moon, 2021) juga mengungkapkan bahwa peningkatan kompetensi juga memberikan peningkatan kepuasan dan motivasi kerja karyawan. Motivasi kerja karyawan ini juga menjadi pendorong peningkatan kinerja.…”
Section: Variable Independent (X) Terhadap Kinerja (Performance) Kary...unclassified